2001
DOI: 10.1097/00000539-200105000-00045
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Efficacy of Tramadol is Impaired by Concurrent Administration of Ondansetron

Abstract: Tramadol has weak opioid properties, and an analgesic effect that is mediated mainly by inhibition of the reuptake of norepinephrine and serotonin (5-hydroxytryptamine [5-HT]) and facilitation of 5-HT release (1,2) at the spinal cord. Because 5-HT3 receptors play a key role in pain transmission at the spinal level (3), the 5-HT3 antagonist ondansetron may decrease the efficacy of tramadol, as suggested in an abstract by Maroof et al. In that study, a small dose of 1 mg/kg tramadol was administered along with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 7 publications
4
56
0
5
Order By: Relevance
“…12 Likewise ondansetron reduces the overall analgesic effect of tramadol probably by blocking spinal 5-HT3 receptors. 13 In patients undergoing various transurethral procedures after effective blockade of serotonin receptor by giving ondansetron before spinal anesthesia showed decreased block level produced by intrathecal lidocaine.…”
mentioning
confidence: 99%
“…12 Likewise ondansetron reduces the overall analgesic effect of tramadol probably by blocking spinal 5-HT3 receptors. 13 In patients undergoing various transurethral procedures after effective blockade of serotonin receptor by giving ondansetron before spinal anesthesia showed decreased block level produced by intrathecal lidocaine.…”
mentioning
confidence: 99%
“…Because tramadol produced less pronounced cardiovascular depression effects (Witte et al 2001), the results in our study suggested that the positive chronotropic effects of tiletamine/ zolazepam probably counterbalance temporarily and partially the bradycardic effect of xylazine (Selmi et al 2003;Kim et al 2007). In our study, blood pressure changed after anaesthetic drug combination administration, but the values were well maintained in the animals.…”
Section: Discussionmentioning
confidence: 52%
“…But it is frequently associated with bradycardia, which could be due to decreased sympathetic activity and/or increased vagal tone (Selmi et al 2003). Tramadol has proven effective in both experimental and clinical pain without causing serious cardiovascular or respiratory adverse effects (Witte et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to perform any meaningful meta-analysis of nausea or vomiting for this study as the outcome was reported inconsistently with different measures and at different time points. Although some studies [4,6] supported the suggestion of an increased incidence of nausea when ondansetron was co-administered with tramadol, the finding was not confirmed among the remainder [5,[7][8][9]11]. Whether or not the co-administration of ondansetron and tramadol results in a higher incidence of nausea and/or vomiting, and if so, whether this is due to a direct effect on the efficacy of ondansetron or secondary to increased tramadol consumption, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Where numerical values of mean and SD results of cumulative tramadol consumption were not supplied within published papers, the author, where available, was contacted by email. Where the information was still not obtained [7][8][9], enlarged-scale visual estimation of the data was undertaken using the figures in the published studies.…”
Section: Methodsmentioning
confidence: 99%